Effects of Rhodiola rosea supplementation on mental performance, physical capacity, and oxidative stress biomarkers in healthy men - Ewa Jówko; Jerzy Sadowski; Barbara Długołęcka; Dariusz Gierczuk; Benedykt Opaszowski; Igor Cieśliński (Elsevier, 2018)
Purpose: The objective of this study was to investigate the effects of chronic Rhodiola rosea (R. rosea) supplementation on mental and physical performance, as well as hormonal and oxidative stress biomarkers. Methods: Twenty-six healthy male students received either R. rosea extract (600 mg/day; RR) or placebo (PL) in a randomized double-blind trial. Prior to supplementation (Term I) and following 4 weeks of supplementation (Term II), the students underwent psychomotor tests for simple and choice reaction time, included in the Vienna Test System. Also, the subjects performed VO2peak test. Blood samples were obtained before and after the test to measure the hormonal profile (cortisol, testosterone, and growth hormone), as well as the biomarkers of oxidative stress (lipid hydroperoxides, total antioxidant capacity, and superoxide dismutase) and muscle damage (creatine kinase). Results: R. rosea ingestion shortened reaction time and total response time. Moreover, a greater relative increase in the number of correct responses was observed in RR group as compared to the PL group. No changes in endurance exercise capacity and hormonal profile were observed after R. rosea ingestion. R. rosea ingestion raised plasma total antioxidant capacity. It did not, however, affect other measured parameters. Conclusion: Chronic R. rosea ingestion does not affect physical performance, but can improve the results of some psychomotor tests (simple and choice reaction time) in young, healthy, and physically active men. The improvements in mental performance, however, at least in our study, seem not to be related to changes in cortisol release or antioxidant activity of R. rosea extract. Thus, the specific mechanisms responsible for these effects still need to be elucidated. Keywords: Cortisol, Endurance capacity, Incremental exercise, Men, Oxidative stress, Simple and choice reaction time, Testosterone